ANALISIS SPASIAL KESESUAIAN DAN EVALUASI LAHAN PERMUKIMAN DI KOTA AMBON - Heinrich Rakuasa; Glendy Somae (Universitas Muhammadiyah Gorontalo, 2022)
The increasing number of residents in Ambon City from year to year which is increasing has an impact on land conversion for the development of residential areas and environmental damage in the future. In connection with this, in the development of residential areas in Ambon City, it is necessary to carry out a spatial analysis of land suitability for settlements to assess the categories of area functions and land suitability for settlements based on physical conditions and the existing RTRW. This study aims to analyze the suitability and evaluation of residential land in Ambon City based on the RTRW of Ambon City in 2011-2031. This research uses Spatial Multi-Criteria Analysis (SMCA) method. The results of the study were then used to evaluate the RTRW of Ambon City 2011-2031. The results of the SMCA analysis show that an area of 13,282, 46 ha is suitable and 2,019, 88 ha is sufficient after the development of residential areas. Based on the results of the RTRW evaluation, there are many deviations in the development of settlements in protected forest areas and there are still many settlements located <100 m from the river border. The results of this study are expected to be a reference and input for the evaluation of the Ambon City RTRW in the future.